The Mechanism by Which Hedgehog Interacting Protein (HHIP) in Cancer-Associated Fibroblasts Regulate the Secretion of Inflammatory Factors Through the JAK1/STAT3 Pathway Affecting Prostate Cancer Stemness [Corrigendum] - Wo Q; Shi L; Shi J; Mao Y; Xie L (Journal of Inflammation Research, 2025)
Wo Q, Shi L, Shi J, Mao Y, Xie L. J Inflamm Res. 2024;17:8659—8680. The authors have advised that Figure 13F on page 8676 is incorrect. Due to an error in image processing during revision, the images for the “CAF + AG490” and “CAF + AG490 + si-NC” groups were mistakenly replaced by the “CAF” group image, resulting in three duplicated images. The correct Figure 13 is as follows.